Strategi Preventif Sengketa Hukum Bisnis pada Kolaborasi Bisnis Milenial di Era Digital - Rizal, Balqis; Safitri, Dinda Maulida; Lestari, Ribi Amelia; Hasyim, Hasyim (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to identify preventive strategies that can be implemented by millennial business actors to avoid legal disputes. The method used is descriptive qualitative with a focus on the role of digital communication in the business legality process and the importance of digital security literacy for business actors. Digital transformation opens up enormous opportunities for the millennial generation to be involved in various business collaborations. This development certainly raises several challenges in the legal field such as in the aspect of intellectual property rights protection, business ownership and partnership agreements. The results of this study indicate that the low understanding of the legal aspects in the digital business world is very often a trigger for disputes between partners. Therefore, synergy between business actors, the government and educational institutions is needed to strengthen the legal capacity of the millennial generation in running their businesses legally and sustainably. Preventive strategies are chosen as a very important foundation in creating a healthy, fair and legally protected digital business ecosystem.